Reduced lipid intake leads to changes in digestive enzymes in the intestine but has minor effects on key enzymes of hepatic intermediary metabolism in rainbow trout (Oncorhynchus mykiss) - S. Ducasse-Cabanot; J. Zambonino-Infante; N. Richard; F. Medale; G. Corraze; M. Mambrini; J. Robin; C. Cahu; S. Kaushik; S. Panserat (Animal, 2007)
For sustainable aquaculture, the removal of marine resource ingredients in fish diets is an important objective. While most studies focus on the replacement of fish oil by vegetable oil, little is known on the nutritional effects of presence (which corresponds to the control diet) or absence of dietary fish oil. We studied fatty acid composition of brush-border membranes and digestive enzyme activities of the intestine and measured the expression and activities of several enzymes involved in the hepatic intermediary metabolism of rainbow trout (Oncorhynchus mykiss) fed for 7 weeks with or without fish oil. The diets were pair-fed to ensure that fish fed either diet had comparable carbohydrate and protein intakes. Absence of fish oil significantly reduced growth rate, protein efficiency and plasma lipid components. Activities of intestinal digestive enzymes were significantly decreased in the anterior intestine in fish fed without fish oil. In liver, dietary fish oil removal did not affect the transcript levels or activities of the main enzymes involved in lipogenesis (fatty acid synthase) and fatty acid β-oxidation (3-hydroxyacyl-CoA dehydrogenase), glycolysis or amino acid oxidation. It lowered the expression of the genes coding for gluconeogenic enzymes (glucose-6-phosphatase and phosphoenolpyruvate carboxykinase), but their enzyme activities were not affected. The activities, but not gene expression of lipogenic enzymes, involved in NADPH and malonyl-CoA formation were also modified after fish oil removal as reflected by higher activities of isocitrate dehydrogenase/glucose-6-phosphate dehydrogenase and acetyl-CoA carboxylase enzymes. Overall, our results indicate that the intestinal digestive capacity was strongly modified by dietary fish oil removal, while hepatic intermediary metabolism was only marginally affected, in fed rainbow trout.